Etika Pangan dalam Al-Qur’an: Analisis Tafsir Tematik atas Konsep Halal–?ayyib, Distribusi Sosial, dan Ketahanan Pangan - Ammar Munir; Abdul Rahman Zain; Hadrawati Abdullah (STAI YAPIS Takalar, 2026)
Food in the Qur’an is not merely understood as a biological necessity, but as part of an ethical system encompassing the dimensions of quality, distribution, and food security. However, existing studies on food from a Qur’anic perspective remain largely partial, often limited to the halal–haram aspect or descriptive analyses that lack integration with a comprehensive social-ethical framework. This study aims to reconstruct the ethics of food in the Qur’an through a thematic exegesis approach (tafs?r maudh?‘?), by examining verses related to the concepts of halal–?ayyib, food distribution to vulnerable groups, and principles of food security. This research employs a qualitative method based on library research, analyzing Qur’anic verses, classical and contemporary exegesis, and relevant academic literature. The findings reveal that Qur’anic food ethics consist of three main pillars: (1) food quality through the concept of halal–?ayyib, which encompasses legality, health, and nutritional value; (2) social distribution as an instrument of justice through the provision of food to vulnerable groups; and (3) food security through principles of long-term planning and sustainable resource management, as reflected in the story of Prophet Yusuf (Joseph). Furthermore, Qur’anic food ethics carry multidimensional axiological implications in the areas of health, spirituality, education, economy, and social solidarity. The novelty of this study lies in reconstructing Qur’anic food ethics as an integrative normative system by combining thematic exegesis, the maq??id al-shar?‘ah framework, and social policy analysis. This study demonstrates that the Qur’anic concept of food can serve as an ethical foundation for formulating social policies oriented toward justice and societal welfare.